The PmrA‐PmrB two‐component system responding to acidic pH and iron controls virulence in the plant pathogen Erwinia carotovora ssp. carotovora - Hyytiäinen, Heidi; Sjöblom, Solveig; Palomäki, Tiina; Tuikkala, Anne; Tapio Palva, E. (Molecular microbiology, 2003)
Summary Efficient response to environmental cues is crucial to successful infection by plant‐pathogenic bacteria such as Erwinia carotovora ssp. carotovora. The expression of the main virulence genes of this pathogen, encoding extracellular enzymes that degrade the plant‐cell wall, is subject to complex regulatory machinery where two‐component systems play an important role. In this paper, we describe for the first time the involvement of the PmrA‐PmrB two‐component system in regulation of virulence in a plant‐pathogenic bacterium. Disruption of pmrB resulted in reduced virulence both in potato and in Arabidopsis. This is apparently due to reduced production of the extracellular enzymes. In contrast, a pmrA mutant exhibited increased levels of these enzymes implying negative regulation of the corresponding genes by PmrA. Furthermore, the pmrB but not pmrA mutant exhibited highly increased resistance to the cationic antimicrobial peptide polymyxin B suggesting alterations in cell surface properties of the mutant. A similar increase of polymyxin resistance was detected in the wild type at mildly acidic pH with low Mg2+. Functional pmrA is essential for bacterial survival on excess iron at acidic pH, regardless of the Mg2+ concentration. We propose that PmrA‐PmrB TCS is involved in controlling of bacterial response to external pH and iron and is crucial for bacterial virulence and survival in planta.